Aftershock zones of large shallow earthquakes: fault dimensions, aftershock area expansion and scaling relations - Henry, C; Das, S (Geophysical Journal International, 2016)
We determine the aftershock areas from relocated hypocentres for 64 dip-slip and eight strike-slip earthquakes in the period 1977-1996 together with those for three recent earthquakes, the 1998 Antarctic plate earthquake, the 1999 Izmit, Turkey earthquake and the 2000 Wharton Basin earthquake. We also include the data for 27 strike-slip earthquakes from Pegler and Das (1996). We find that the location of the hypocentre is essentially random along strike for both strike-slip and dip-slip earthquakes. Subduction zone earthquakes appear to initiate more frequently towards the down-dip edge of the fault, whereas the non-subduction zone dip-slip earthquakes do not have any preferred depth of initiation. The aftershock zones of subduction zone earthquakes often expand substantially along strike and up dip but far less in the down-dip direction, whereas those for non-subduction zone earthquakes do not expand significantly in either the up- or the down-dip direction. Subduction zone thrust earthquakes have larger and more numerous aftershocks than earthquakes in all other tectonic settings. For strike-slip earthquakes, we find that slip increases at least linearly with length. For dip-slip earthquakes, we find that the ratio of length to width increases systematically with length for lengths > 40 km, indicating that there is some restriction on fault width; slip is found to be proportional to length over the moment range 1017 N m < M0 < 3 × 1021 N m, taking our data in conjunction with the data of Wells and Coppersmith (1994).